Digital History Goes East: A Database Description of Cultural Heritage Assets: "Project Monuments and Artworks in East Central Europe Research Infrastructure". (3rd April 2019) - Kłoda, Emilia; Stanicka-Brzezicka, Ksenia
Abstract : The project "Monuments and Artworks in East Central Europe Research Infrastructure" exemplifies introducing methods and tools of digital humanities to art-historical problems in multilingual and culturally diverse milieu. East Central Europe is a region with historically changing borders and different national cultures of knowledge. For such a region, a proper transnational scientific infrastructure is vital for the adequate description and classification of art-historical monuments, and dynamic networks of actors and cultural phenomena. Drawing on our project experience, we argue that the model of knowledge created through the process of data modelling and setting standards for digital images can be seen as an interpretative and epistemological frame for research. This paper analyses the transnational integration of catalogued data into the infrastructure through a semantic data model. We tackle the question of implementation of multilingual external vocabularies and authority control in the database. The method of indexing photos in the context of the material turn is another crucial issue in the infrastructure. In addition, this paper underlines practical challenges of the project such as: involvement in an international network of collaborators, legal requirements, and copyright.